Elective ICU admission after major surgery: can too much support be futile? - Zampieri, Fernando G. (Journal of Thoracic Disease, 2018)
Elective ICU admissions represent an important part of all ICU admissions worldwide (1,2). Considering the significant mortality and morbidity associated with major surgery and its complications, it is conceivable that admission to an environment with intensive monitoring and with a staff capable of immediate recognition and treatment of abnormalities could reduce mortality (1). This concept, albeit based on a solid rationale, has been recently challenged in large cohort studies (3).